Somatic Dimorphism in Cercariae of a Bird Schistosome - Soldánová, Miroslava; Kundid, Petra; Scholz, Tomáš; Kristoffersen, Roar; Knudsen, Rune (Pathogens (Basel, Switzerland), 2022)
Phenotypic polymorphism is a commonly observed phenomenon in nature, but extremely rare in free-living stages of parasites. We describe a unique case of somatic polymorphism in conspecific cercariae of the bird schistosome Trichobilharzia sp. "peregra", in which two morphs, conspicuously different in their size, were released from a single Radix balthica snail. A detailed morphometric analysis that included multiple morphological parameters taken from 105 live and formalin-fixed cercariae isolated from several naturally infected snails provided reliable evidence for a division of all cercariae into two size groups that contained either large or small individuals. Large morph (total body length of 1368 and 1339 μm for live and formalin-fixed samples, respectively) differed significantly nearly in all morphological characteristics compared to small cercariae (total body length of 976 and 898 μm for live and formalin samples, respectively), regardless of the fixation method. Furthermore, we observed that small individuals represent the normal/commonly occurring phenotype in snail populations. The probable causes and consequences of generating an alternative, much larger phenotype in the parasite infrapopulation are discussed in the context of transmission ecology as possible benefits and disadvantages facilitating or preventing the successful completion of the life cycle.
Keywords: polymorphism; bird schistosome; trematodes; phenotype; cercariae; Trichobilharzia